Construção de um aparato de baixo custo para medir ângulo de contato - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2017)
This work aimed to build a low cost apparatus capable of measuring contact angle, because the surface area has been gaining more and more space and arousing more interest by multinationals, however, an apparatus capable of measuring contact angle has a high cost and not everyone can afford this apparatus, so the question came up, how to build a low cost apparatus capable of measuring contact angle? The main objective is to measure the contact angle between surfaces. To build it we used scrap material as well as some other articles from haberdashery and pieces such as guitar tuning for example. After the construction, the data was collected and, in a quantitative way using statistics, the contact angle values were found. The apparatus showed itself capable of performing contact angle measurements where the values obtained in this work were 45.3º ± 0.9º and 45.2º ± 1.5º between water and glass, 158.5º ± 0.3º and 157.6º ± 0.9º between water and Thalia Geniculata and 167.8º ± 1.4º and 160.4º ± 4º between water and the plant Colocasia Antiquorum Schottpara (tajá).
Keywords: Ângulo de contato; Superhidrofóbico; Aparato de baixo custo; CNPQ::CIENCIAS EXATAS E DA TERRA